THE INHERITANCE OF PAIN BETWEEN DAUGHTERS AND MOTHERS IN MANJU KAPUR’S DIFFICULT DAUGHTERS - Kashyap, Aparna; Dr. Richa (ShodhGyan-NU: Journal of Literature and Culture Studies, 2025)
Difficult Daughters by Manju Kapur explores the feelings and psychological issues experienced by three generations of women in India Kasturi, Virmati, and Ida, who are striving to cope with the vagaries of personal freedom and the demands of the society and family. The novel touches the theme of generational conflicts inside their family, the battles of female independence, and the national situation of independence. In the face of such assertion of independence, the characters are faced with both individual and social obstacles resulting in emotional and psychological crisis. This paper analyzes how Kapur employs these struggles to show us the prices of freedom and self-realization in a patriarchal society, which illuminates the intersections of individual desires, cultural change and the legacy of generational pain. Finally, the novel highlights the uncertainties that women have to go through in their pursuit of independence as individuals and a nation.